2010
DOI: 10.1016/j.ejcts.2009.06.052
|View full text |Cite
|
Sign up to set email alerts
|

Early timing of surgical intervention in patients with Ebstein's anomaly predicts superior long-term outcome☆

Abstract: Repair, as opposed to replacement, is feasible in the vast majority of patients presenting with Ebstein's anomaly with a low early mortality rate. Outcome, in terms of survival and freedom from re-operation in the long term is determined by the clinical state at the time of surgery. Therefore, timely operation is warranted before significant cardiomegaly develops and functional status deteriorates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 22 publications
0
40
0
Order By: Relevance
“…The mean time between initial surgery and redo in our series was 13.4 ± 10.6 years. Re-operation rates of 9 and 20% were reported by Chauvaud [5] and Badiu et al [8], respectively. Long-term follow-up in operated patients with Ebstein’s anomaly is mandatory, as redo surgery in adulthood is not rare.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…The mean time between initial surgery and redo in our series was 13.4 ± 10.6 years. Re-operation rates of 9 and 20% were reported by Chauvaud [5] and Badiu et al [8], respectively. Long-term follow-up in operated patients with Ebstein’s anomaly is mandatory, as redo surgery in adulthood is not rare.…”
Section: Discussionmentioning
confidence: 71%
“…The reoperation rate in this series was 9% [5]. Today, early mortality rates as low as 1.6% have been reported [8]. The majority of patients in our study underwent valve repair.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Patients who had surgery at institutions other than the present one, and for whom data on the surgery, or echocardiography or clinical records were ity. 8 They suggested that, even in an asymptomatic or minimally symptomatic patient, early surgery must be performed before cardiomegaly develops and functional class worsens. In contrast, other authors consider that surgery should be delayed until symptoms appear, cyanosis becomes evident or paradoxical embolism occurs.…”
Section: Methodsmentioning
confidence: 99%